Sensing high frequency sub-nanometer vibrations using optical coherence tomography with real-time profilometry of multiple inner layers. (April 2020) - Nandakumar, Hari; Mallick, Satya Prasanna; Srivastava, Shailesh
Highlights: A new technique for OCT vibrometry is proposed, based on time averaged sampling in the spectral domain. Can use low-cost cameras for sensing few-picometer inner layer vibration amplitudes unrestricted by Nyquist limit. Proof-of-principle demo with a low-cost, low SNR, spectral domain OCT instrument built using off-the-shelf components. Inner layer vibration amplitude sensing of 270 pm to 160 nm over 1 kHz to 20 kHz is demonstrated. Graphical abstract: Abstract: A robust technique for vibration sensing using Optical Coherence Tomography is introduced, which can yield nanometer- and sub-nanometer-scale vibration measurements for multiple inner layers simultaneously, even with low signal to noise ratio (SNR) signals from low cost devices. Constructing a camera-based parallel spectral domain optical coherence tomography device with just 40 dB SNR, we demonstrate as proof-of-principle, how our technique can work with vibration amplitudes over three orders of magnitude, from hundreds of picometers to hundreds of nanometers. Our technique is unrestricted by the Nyquist sampling limit. This makes it suitable for measuring amplitudes of even MHz frequency vibrations which are challenging to measure with conventional phase-sensitive methods. We believe our technique will find vital applications for in vivo medical diagnostics, especially of the middle ear.